2020
DOI: 10.3390/ijms21176362
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Adaptation to Environmental Cues by Symmetric and Asymmetric Division Modes of Intestinal Stem Cells

Abstract: Tissues must adapt to the different external stimuli so that organisms can survive in their environments. The intestine is a vital organ involved in food processing and absorption, as well as in innate immune response. Its adaptation to environmental cues such as diet and biotic/abiotic stress involves regulation of the proliferative rate and a switch of division mode (asymmetric versus symmetric) of intestinal stem cells (ISC). In this review, we outline the current comprehension of the physiological and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Environmental cues can cause ISCs to switch from homeostatic asymmetric stem cell division (in which one daughter cell retains stemness and the other differentiates) to symmetric division (in which both daughter cells retain stemness) [ 69 ]. This involves changing the orientation of ISC mitotic spindle relative to the plane of the epithelium from an oblique angle (asymmetric) to parallel (symmetric) [ 70 ]. In Drosophila ISCs, JNK induces symmetric cell divisions by phosphorylating and recruiting Wdr62 to the centrosome and by repressing transcription of Kif1a, a kinesin implicated in promoting asymmetric divisions [ 71 , 72 ].…”
Section: Jnk Signaling In Stress Responses and Aging In The Drosophila Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…Environmental cues can cause ISCs to switch from homeostatic asymmetric stem cell division (in which one daughter cell retains stemness and the other differentiates) to symmetric division (in which both daughter cells retain stemness) [ 69 ]. This involves changing the orientation of ISC mitotic spindle relative to the plane of the epithelium from an oblique angle (asymmetric) to parallel (symmetric) [ 70 ]. In Drosophila ISCs, JNK induces symmetric cell divisions by phosphorylating and recruiting Wdr62 to the centrosome and by repressing transcription of Kif1a, a kinesin implicated in promoting asymmetric divisions [ 71 , 72 ].…”
Section: Jnk Signaling In Stress Responses and Aging In The Drosophila Intestinementioning
confidence: 99%
“…However, when symmetric divisions become chronic, for example, during stress or aging, tissue homeostasis is compromised and the lifespan is shortened (see below). While spindle reorientation favoring symmetric divisions has been observed in mouse ISCs, it is not known whether JNK regulates this process [ 70 , 73 ].…”
Section: Jnk Signaling In Stress Responses and Aging In The Drosophila Intestinementioning
confidence: 99%
“…The mode of stem cell division in the gut is a controversial topic—both symmetric and asymmetric stem cell division are proposed to contribute to homeostasis. The division pattern of stem cells is regulated by intrinsic cell polarity cues, cell shape and/or environmental signals [ 122 , 123 , 124 ]. Biased spindle orientation in asymmetric cell divisions will either couple intrinsically the orientation of the division plane with the asymmetric segregation of cell fate determinants or change the respective surroundings encountered by the two daughter cells [ 62 , 125 , 126 , 127 ].…”
Section: The Tumour Suppressor Apc a Master Rmentioning
confidence: 99%
“…Yet, more recently, a counter-proposal has favoured instead an asymmetric cell division-dominant neutral drift model also validated in vivo [ 129 ]. These contrasting findings could be related to experimental details, e.g., nutrient availability, harsh environment or aging [ 124 , 130 ]. Indeed, the frequency of self-renewing asymmetric division changes as a function of age to respond to developmental or local effects as well as stress associated with micro-injuries both in mice and flies [ 7 ].…”
Section: The Tumour Suppressor Apc a Master Rmentioning
confidence: 99%
“…Previous studies have shown that the proliferation and differentiation of ISCs under physiological and stressed conditions are regulated by many signaling pathways including the Notch, Wingless (Wg), Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT), Epidermal Growth Factor Receptor (EGFR), Hippo (Hpo), Insulin, Hedgehog (Hh), and Bone Morphogenetic Protein (BMP) pathways (see reviews by Colombani and Andersen, 2020 ; Gervais and Bardin, 2017 ; Guo et al, 2016 ; Jiang et al, 2016 ; Joly and Rousset, 2020 ; and references therein). The evolutionarily conserved Notch signaling pathway plays essential roles in the control of cell proliferation and specification/differentiation during animal development ( Artavanis-Tsakonas and Muskavitch, 2010 ).…”
Section: Introductionmentioning
confidence: 99%